Enantioselective Synthesis of Fmoc-Protected (2S,3R)-3,4-Dimethyl-2-(methylamino)pentanoic Acid - Yu, Po-Cheng; Ansari, Nurul; Taylor, Jerry; Velazquez, Francisco; Nittoli, Thomas (Synlett, 2025)
The first enantioselective synthesis of the Fmoc-protected rare amino acid, 3,4-dimethyl-2-(methylamino)pentanoic acid, is disclosed. The synthesis utilized the chiral oxazolidinone to introduce the first chiral center (>95:5 ee), and then swapped the auxiliary to Ellman’s N-sulfinylimine for setting up the chiral α-amino group (95:5 dr). The newly formed chiral centers were confirmed by X-ray crystallography. With this unique amino acid on hand, naturally occurring macrocyclic peptides will become synthetically accessible.
Keywords: enantioselective synthesis; amino acid; etamycins A; triostin C; echinomycin C